2021
DOI: 10.1186/s10194-021-01368-7
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of headache impact and health-related quality of life in migraine patients after cessation of preventive treatment with CGRP(−receptor) antibodies

Abstract: Background Migraine preventive treatment with CGRP(−receptor) monoclonal antibodies (mAbs) has a positive effect on patients’ health-related quality of life (HRQoL). The German treatment guidelines recommend discontinuing successful treatment with CGRP(−receptor) mAbs after 6–12 months. We aimed to evaluate headache-specific and generic HRQoL for three months after discontinuation of CGRP(−receptor) mAb treatment. Methods We conducted a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 50 publications
0
17
0
4
Order By: Relevance
“…CGRP/(R)-AKs: Erenumab, Galcanezumab, Fremanezumab Eptinezumab Zusammenfassend zeigen die bisherigen Daten (10 Studien, 2171 Patienten), dass nach Absetzen einer erfolgreichen Migräneprophylaxe mit CGRP/(R)-AK bei der Mehrzahl der Patienten wieder eine schrittweise Zunahme der Migränefrequenz, der migränebedingten Alltagseinschränkungen und eine Zunahme des Bedarfs an Akutmedikation eintritt [30][31][32][33][34][35][36][37][38][39]. Die Studien variieren in der Methodik (retrospektiv versus prospektiv, kontrolliert versus "realworld"-Daten, Fallzahlen, Therapie-und Nachbeobachtungszeiträume, chronische versus episodische Migräne, mit versus ohne Medikamentenübergebrauch, untersuchte Wirkstoffe), was die Aussagekraft direkter Vergleiche einschränkt.…”
Section: Spezifische Prophylaxemedikamenteunclassified
See 1 more Smart Citation
“…CGRP/(R)-AKs: Erenumab, Galcanezumab, Fremanezumab Eptinezumab Zusammenfassend zeigen die bisherigen Daten (10 Studien, 2171 Patienten), dass nach Absetzen einer erfolgreichen Migräneprophylaxe mit CGRP/(R)-AK bei der Mehrzahl der Patienten wieder eine schrittweise Zunahme der Migränefrequenz, der migränebedingten Alltagseinschränkungen und eine Zunahme des Bedarfs an Akutmedikation eintritt [30][31][32][33][34][35][36][37][38][39]. Die Studien variieren in der Methodik (retrospektiv versus prospektiv, kontrolliert versus "realworld"-Daten, Fallzahlen, Therapie-und Nachbeobachtungszeiträume, chronische versus episodische Migräne, mit versus ohne Medikamentenübergebrauch, untersuchte Wirkstoffe), was die Aussagekraft direkter Vergleiche einschränkt.…”
Section: Spezifische Prophylaxemedikamenteunclassified
“…In 3 der 10 Publikationen wurde berichtet, dass auch nach 3 Monaten Therapiepause die mittleren MMDs zwar signifikant zum letzten Therapiemonat anstiegen, jedoch weiterhin geringer waren als zur Baseline [30,31,40]. Hier sind Studiendaten zur gesundheitsbezogenen Lebensqualität während der Therapiepause mit CGRP/(R)-AK zu beachten, die bereits in Woche 8-16 nach Therapieende eine signifikante Zunahme der kopfschmerzbedingten Einschränkung der Alltagsaktivitäten und der Lebensqualität zeigen [37]. Ist eine Fortsetzung der Therapie mit CGRP/(R)-AK nötig, so belegen die dazu bislang publizierten Studien, dass die Mehrzahl der Patienten nach Wiederbeginn der CGRP/(R)-AK-Therapie genauso gut wie in der initialen Behandlung ansprechen [30,32,35].…”
Section: Spezifische Prophylaxemedikamenteunclassified
“…These treatments have persistently confirmed their efficacy in phase 3 trials [162][163][164][165][166][167][168][169][170][171][172][173][174], with convenient dosing, faster onset of efficacy and mild to moderate adverse events [175,176]. Further, real-world studies have shown improvement with mABs and worsening of migraine frequency following discontinuation, with most patients resuming treatment as soon as possible following breaks due to regulatory restrictions [177][178][179][180]. The European Headache Federation currently recommends CGRP mABs as a first-line option for migraine prevention, with treatment to be continued as long as needed [181], although in most jurisdictions, this is not possible to operationalize easily.…”
Section: Preventive Treatmentsmentioning
confidence: 99%
“…En segundo lugar, se han practicado varios estudios de vida real, en relación con las suspensiones obligatorias en algunos países europeos de los tratamientos con anticuerpos anti-PRGC tras 6-12 meses (Tabla 2). El empeoramiento de la migraña objetivado en estos estudios tras la retirada parece ser más severo de lo comunicado en los pacientes de los ensayos clínicos 38,39,40,41,44 . Se han reportado empeoramientos rápidos ya desde el primer mes tras la retirada 40 .…”
Section: Evolución De La Migraña Tras La Retirada De Los Anticuerpos ...unclassified
“…En algunos se objetiva una frecuencia de DMM equiparable a los registros basales de los pacientes a los tres meses sin tratamiento 39,45 y en otros a los cuatro meses 41 . Tras la retirada del tratamiento aumenta el consumo de medicación aguda y la insatisfacción del pacien-te 39 , empeoran las escalas de calidad de vida e impacto de la cefalea 38 , y una proporción creciente de pacientes vuelve a cumplir criterios de migraña crónica y de uso excesivo de medicación sintomática 39 . En un estudio de Raffaelli et al, además, se objetivó un empeoramiento más rápido de los pacientes con erenumab (ya el segundo mes tras la retirada) respecto a galcanezumab y fremanezumab (a partir del tercer mes), quizás por la vida media más corta del primero 41 .…”
Section: Evolución De La Migraña Tras La Retirada De Los Anticuerpos ...unclassified